Skabies - sri ardila nirainiwati (Saintika Medika, 2011)
Scabies is a human skin infestation caused by the infestations and sensitization of the parasitic Sarcoptes scabiei var. hominis.Scabies has been spread around in the world especially in the tropics and subtropics. There are several types of clinical manifestation. Thediagnosis is based on a history of itching at night, a typical distribution of lesions, history of similiar complaints in other family members.Diagnosis must be established with the discovery of mites on microscopic examination that can be done in various ways. The are numberof topical treatments for scabies. The selections of drug based on effectivenes potential toxicity of drugs and how to use the proper.